Web-Based Spare Parts Expenditure Recording Portal with Read-Only Pull from ERP Infor (PT CBI Case Study) - kurnia, Alvito Kurnia Fahrio (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
A companion portal for spare parts management was developed at the PT Century Batteries Indonesia (PT CBI) warehouse to address manual record keeping that is prone to discrepancies and difficult to trace. This article focuses on two key aspects: a checkout flow that validates expenditure amounts against Portal stock, and a reconciliation mechanism that pulls on-hand data from Infor's ERP read-only system to maintain ERP data integrity. The system was developed following the Extreme Programming (XP) methodology with short iterations and regular feedback from warehouse users. Black-box testing and UAT (User-to-User) testing demonstrated that the main flow functioned as expected; all assessed features were accepted with scores of 4.1–4.8. Consequently, discrepancies were detected more quickly and addressed through adjustments in Infor; the Portal then pulled back on-hand to ensure consistency. These results demonstrate that the "checkout in Portal → adjustment in Infor → pulled back on-hand (read-only)" pattern effectively reduces errors caused by manual recording while improving transaction traceability in the spare parts expenditure process in the warehouse environment. Keywords : warehouse management; spare part checkout; Infor ERP; read-only integration; Extreme Programming;